2008
DOI: 10.1159/000149719
|View full text |Cite
|
Sign up to set email alerts
|

Sanguinarine, a Benzophenanthridine Alkaloid, Induces Apoptosis in MDA-MB-231 Human Breast Carcinoma Cells through a Reactive Oxygen Species-Mediated Mitochondrial Pathway

Abstract: Background: Sanguinarine is a benzophenanthridine alkaloid that is known to have antimicrobial, anti-inflammatory, antioxidant and anticancer properties. In this study, we examined the effects of this compound on reactive oxygen species (ROS) production and the association of these effects with apoptotic tumor cell death using a human breast carcinoma MDA-MB-231 cell line. Methods: Cytotoxicity was evaluated by trypan blue exclusion methods. Apoptosis was detected using DAPI staining, agarose gel electrophores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 41 publications
2
47
0
4
Order By: Relevance
“…In detail, it has been reported that micromolar concentrations of sanguinarine are capable of inhibiting tumor cell growth, and this inhibitory effect is associated with cell cycle arrest and induction of apoptosis [19][20][21][22] . The anti-proliferative and/ or pro-apoptotic activities of sanguinarine have been demonstrated in in vitro studies on several cancer cell types including epidermal [23] , keratinocyte [24,25] , prostate [26][27][28] , cervical [29] , breast [20,[30][31][32][33] , leukaemia [34,35] , lymphoma [36] , melanoma [37][38][39] , colon [40,41] , colorectal [21] , gastric [42] , pancreatic [19] , lung [22] , neuroendocrine [43] , osteosarcoma [44] , and human neuroblastoma cells [45] . By contrast, there are few studies on the in vivo effectiveness of sanguinarine administration per os [46,47] in animal tumor models [33,48] .…”
Section: Sanguinarine Induces Apoptosis In Tumor Cellsmentioning
confidence: 99%
“…In detail, it has been reported that micromolar concentrations of sanguinarine are capable of inhibiting tumor cell growth, and this inhibitory effect is associated with cell cycle arrest and induction of apoptosis [19][20][21][22] . The anti-proliferative and/ or pro-apoptotic activities of sanguinarine have been demonstrated in in vitro studies on several cancer cell types including epidermal [23] , keratinocyte [24,25] , prostate [26][27][28] , cervical [29] , breast [20,[30][31][32][33] , leukaemia [34,35] , lymphoma [36] , melanoma [37][38][39] , colon [40,41] , colorectal [21] , gastric [42] , pancreatic [19] , lung [22] , neuroendocrine [43] , osteosarcoma [44] , and human neuroblastoma cells [45] . By contrast, there are few studies on the in vivo effectiveness of sanguinarine administration per os [46,47] in animal tumor models [33,48] .…”
Section: Sanguinarine Induces Apoptosis In Tumor Cellsmentioning
confidence: 99%
“…[16,20,23,24,26]. 최근 본 연구실의 결과에 의하면, sanguinarine은 교아종(glioblastoma) 세포에서 mitogen activated 생성 의존적 미토콘드리아 활성화를 통하여 일어났음을 알 수 있었고 [7], 인체 유방암세포의 전이 억제는 치밀 결합(tight junction)의 활성 증가와 matrix metalloproteinase 활성 증가 와 연관성이 있었다 [6]. 아울러 인체 방광암과 대장암세포에서 sanguinarine에 의한 apoptosis 유발은 early growth response gene-1 전사활성 증대를 통한 ROS 생성 의존적이었음을 보고 한 바 있다 [13,14].…”
Section: 서 론unclassified
“…아울러 인체 방광암과 대장암세포에서 sanguinarine에 의한 apoptosis 유발은 early growth response gene-1 전사활성 증대를 통한 ROS 생성 의존적이었음을 보고 한 바 있다 [13,14]. 특히 sanguinarine은 인체 위암세포에서 TRAIL 매개 apoptosis를 촉진할 수 있음 확인한 바 있는데, 이 과정은 PI3K/Akt 경로 억제 및 caspase-3의 활성 증가가 관여하고 있음을 알 수 있었으며 [5,7,12,16,21], 이러한 TRAIL 감수성 증대는 유방암세포에서도 확인된 바 있다 [21]. RNAs were isolated and reverse-transcribed.…”
Section: 서 론unclassified
See 1 more Smart Citation
“…Its principle medicinal use to date is in dental products based on its anti-bacterial, anti-fungal, and anti-inflammatory activities, which reduce both gingival inflammation and supragingival plaque formation (Godowski, 1989;Kuftinec et al, 1990;Laster and Lobene, 1990). Several recent studies have showed that sanguinarine, at micromolar concentration, inhibits the growth of cancer cells, and this inhibition of growth is associated with cell cycle arrest and the stimulation of apoptosis (Ahsan et al, 2007;Choi et al, 2008;Han et al, 2013a;Jang et al, 2009). The aim of this study is to determine in vitro effect of sanguinarine against neuroblastoma and to question which apoptotic genes contributes its apoptotic effect.…”
Section: Introductionmentioning
confidence: 98%